Authoring pervasive multimodal user interfaces. (2nd May 2008) - Paterno, Fabio; Santoro, Carmen; Mantyjarvi, Jani; Mori, Giulio; , Sandro Sansone
In this paper, we present an environment for authoring pervasive multimodal user interfaces. It is composed of a set of XML-based languages, transformations among such languages, and an authoring tool. It provides designers with the possibility of designing interfaces for a wide set of platforms, which support various modalities. We describe how the environment has deeply changed from the initial mono-modal, web-oriented environment and provide example applications for a number of platforms.